The Balanced Scorecard: Judgmental Effects of Common and Unique Performance Measures - Lipe, Marlys Gascho; Salterio, Steven E. (The Accounting Review, 2000)
The balanced scorecard is a new tool that complements traditional measures of business unit performance. The scorecard contains a diverse set of performance measures, including financial performance, customer relations, internal business processes, and learning and growth. Advocates of the balanced scorecard suggest that each unit in the organization should develop and use its own scorecard, choosing measures that capture the unit's business strategy. Our study examines judgmental effects of the balanced scorecard—specifically, how balanced scorecards that include some measures common to multiple units and other measures that are unique to a particular unit affect superiors' evaluations of that unit's performance. Our test shows that only the common measures affect the superiors' evaluations. We discuss the implications of this result for research and practice.